Recursos mediacionais: possibilidades de utilização na identificação de estressores em pré-escolares - Zumstein, Luciana de Souza (2009)
This study aims to understand aspects related to children stress through the use of mediating resources. In order to achieve that goal, semi-structured interviews with pre-school children´s mothers were carried out, besides applying the stressors sources scale to the child under childhood stress. To perform the collection of data from the children, workshops were organized and a tool called "The beasts are under stress" was designed, containing a story whose theme was related to the stress, and a mat with the story characters; that tool assumed the nature of a mediating resource and the researchers were trained under the mediating criteria, present in "Mediated Intervention for Sensitizing Caregivers - MISC, such as: focusing, expansion, meaning mediation, reward and self-regulation. After the interviews with the mothers and the workshops with the children were performed and recorded, the transcription and grading of the applied scale was done. The results obtained through the scale with the mothers indicated a high possibility of the participant children to be undergoing stressing situations with strong possibility of psychic and physical illness. However, after analysing the data obtained from the children, some incongruity between the data was noted, since only one of the sixteen participant children showed some symptoms of stress. Another finding of this study came from the possibility of using the designed tool as a form of finding out what the children knew about the stress, and, at the same time intervene to enable the child to express the several indicative form of stress. The research was conducted with 16 children around 4 or 5 years old. It is important to clear that the referred tool was adequate to be used with the five-year-olds, whereas the youngers needed new studies for the adequate implementation of the material. New studies will also have to be carried out to understand the dissonance between the mothers´data and the children´s ones. In this sense it is worth showing to the public what a stress indicator really is and what is expected in terms of human development in childhood.